Health literacy and cancer screening behaviors among community-dwelling female adults in Taiwan. Issue 5 (28th May 2021) - Huang, Chi-Hsien; Lo, Yen-Ju; Kuo, Kuang-Ming; Lu, I-Cheng; Wu, Hsing; Hsieh, Ming-Ta; Liu, I-Ting; Lin, Yu-Ching; Lai, Yu-Cheng; Huang, Ru-Yi; Hung, Wei-Chieh; Lin, Chi-Wei
ABSTRACT: This study was designed to explore the association among health literacy and cancer screening behaviors in Taiwanese females. A total of 353 community-dwelling females were recruited in this cross-sectional study from February to October 2015. Demographic, socioeconomic and personal behavior variables including physical activity, community activity, smoking, alcohol consumption, and betel nut chewing were recorded. Health literacy was evaluated using the Mandarin version of the European Health Literacy Survey Questionnaire. Data on screening behaviors for cervical, breast and colorectal cancers were confirmed by the Taiwanese National eHealth Database. Most respondents with inadequate or problematic general health literacy had no or irregular screening behaviors for cervical, breast and colorectal cancers. In multivariable regression analysis, women with inadequate health literacy were at a greater risk (Odds ratio = 5.71; 95% CI: 1.40–23.26) of having no previous Pap smear screening or >3 years screening interval regardless of education level. However, this association was not detected for breast or colorectal cancer. Women with inadequate health literacy were more likely to have irregular cervical cancer screening, however no associations among health literacy and breast or colorectal cancer were detected. The impact of health literacy on cancer screening behavior warrants further attention and research.